Mauritius and Risk of Debt Crises: Evidence from Dynamic Stochastic Model and Arima Forecast - ADEDOKUN, Adebayo (International Journal of Scientific Research and Management (IJSRM), 2017)
The paper employs dynamic stochastic approach and autoregressive integrated moving average (ARIMA)model to investigate the external debt status of Mauritius, following recent weak export performances andinsinuation of debt crises. The study establishes that, Mauritius was free of debt crisis over the years tillmid-2000s when the debt crises began to set in and escalated since 2009 till date. The paper also foundthat debt increase will persist till 2022, before it will stabilize and remain steady above the optimal sizerequire for economic probity. The study therefore suggests economic overhauling of managementstrategies as against the current palliative measures introduced by the government.